Asuhan Akupunktur Pada Anak Hiperaktif di Medical Bintaro Jakarta Selatan - M Supriadi Dayan Matondang; Leny Candra Kurniawan; Mayang Wulandari; Ikhwan Abdullah (Malahayati Nursing Journal, 2026)
ABSTRACT Attention Deficit Hyperactivity Disorder (ADHD) in children is a disorder characterized by difficulties in maintaining focus, excessive activity, and impulsive behavior. Acupuncture therapy can be an alternative treatment option due to its minimal side effects, especially for patients who are unable to use medication or who have low tolerance to drug-related side effects. This study was conducted as a single case study over six therapy sessions involving one male child participant aged 11 years, a sixth-grade elementary school student, who had experienced ADHD since the age of six. Data collection techniques included observation (Wang), interviews (Wen), listening and smelling (Wen), and palpation (Qie), in accordance with the standards of Traditional Chinese Medicine (TCM). The selection of acupuncture points was based on the syndromes of Spleen Qi Deficiency and Kidney Yin Deficiency, with therapeutic principles focused on calming the Shen and tonifying Spleen Qi and Kidney Yin. The evaluation results showed that acupuncture therapy, accompanied by recommendations for parents to maintain a healthy lifestyle and encourage positive activities for the child, and implemented in a planned manner in accordance with TCM principles, was holistically effective in helping control hyperactivity, improve concentration, and stabilize emotions in the participant with ADHD. Keywords: Attention Deficit Hyperactivity Disorder, Hyperactive Children, Acupuncture Therapy. ABSTRAK Attention Deficit Hyperactivity Disorder (ADHD) Pada Anak adalah gangguan kesulitan dalam fokus, kegiatan yang terlalu aktif, serta perilaku yang impulsive. Terapi akupunktur dapat menjadi pilihan dikarenakan efek samping yang minimal terutama bagi penderita yang tidak dapat menggunakan obat atau tidak memiliki toleransi terhadap gejala efek samping obat-obatan. Penelitian dilakukan dalam bentuk studi kasus tunggal selama enam sesi terapi pada satu anak sebagai partisipan laki-laki berusia 11 tahun kelas 6 SD yang mengalami ADHD sejak usia 6 tahun. Teknik pengumpulan data meliputi observasi (Wang), wawancara (Wen), pendengaran dan penciuman (Wen), dan perabaan (Qie) sesuai standar ilmu pengobatan Tiongkok. Pemilihan titik akupunktur didasarkan pada sindrom Defisiensi Qi Limpa dan Yin Ginjal dengan prinsip terapi yang diterapkan adalah Menenangkan Shen, Tonifikasi Qi Limpa Yin Ginjal. Hasil evaluasi Terapi akupunktur yang disertai anjuran kepada orang tua untuk menjaga pola hidup sehat dan kegiatan positif bagi anak, serta dilaksanakan secara terencana dan sesuai prinsip TCM, terbukti efektif secara holistik dalam membantu mengontrol hiperaktivitas, meningkatkan konsentrasi, dan menstabilkan emosi pada partisipan dengan ADHD. Kata Kunci: Attention Deficit Hyperactivity Disorder, Anak Hiperaktif, Terapi Akupunktur.